PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 023905 KEBUN LADA - HUTAURUK, PINDO (Jurnal Ilmiah Aquinas, 2019)
The purpose of this study was to improve the mathematics learning outcomes of class V students of SD Negeri 023905 Kebun Lada by applying the inquiry method. This research is Classroom Action Research (CAR) which consists of 2 cycles and each cycle consists of: 1) planning, 2) implementation, 3) observation, and 4) reflection. Data collection techniques are carried out by observing activities and learning outcomes tests. The results showed an increase in learning outcomes of Class V students of SD Negeri 023905 Kebun Lada. It can be seen from the results of the implementation of teacher activity learning that it increased from 70% with a fairly good category in the first cycle to 85% with a good category in the second cycle, while from the observation the implementation of student learning activities increased from 65% to the poor category in the first cycle 85% in the good category in cycle II. Furthermore, classical learning completeness of students has increased from 63.64% in the first cycle to 90.91% in the second cycle.